1994
DOI: 10.1093/bja/73.2.194
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dose on suxamethonium-induced muscle damage

Abstract: We have examined postoperative muscle pain and early increases in serum concentrations of myoglobin after administration of suxamethonium to see if these changes were dependent on the dose of drug. Thirty ASA I and II adult patients undergoing day-case surgery received a standard anaesthetic technique, including one of three doses of suxamethonium: 0.5, 1.5 or 3.0 mg kg-1. The incidence of postoperative myalgia and the severity of fasciculations were greater after suxamethonium 1.5 mg kg-1 than after a dose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…The increase we observed in plasma myoglobin concentration after succinylcholine administration in nonusers was similar to that reported previously by other investigators. 15 We also found that the increase in myoglobin concentrations after succinylcholine administration at 5 and 20 min was slightly higher in statin users than in nonusers. Myoglobin concentrations increased considerably over 24 h; however, the absolute values and increases were similar in the two groups.…”
Section: Discussionsupporting
confidence: 50%
“…The increase we observed in plasma myoglobin concentration after succinylcholine administration in nonusers was similar to that reported previously by other investigators. 15 We also found that the increase in myoglobin concentrations after succinylcholine administration at 5 and 20 min was slightly higher in statin users than in nonusers. Myoglobin concentrations increased considerably over 24 h; however, the absolute values and increases were similar in the two groups.…”
Section: Discussionsupporting
confidence: 50%
“…The absence of a progressive dose response for severity of fasciculations associated with succinylcholine suggests that increasing the dose above 1.5 mg.kg −1 might reduce the severity of myalgia by producing more synchronous muscle contractions, thereby reducing the shearing forces on muscle spindles. It has been shown that a dose of 3 mg.kg −1 provided a better combination of intubating conditions and minimal postoperative myalgia than the two lower doses (0.5 and 1.5 mg.kg −1 ) [85]. However, uncertainty about the effects of the large dose on other side‐effects, such as potassium concentrations and intragastric and intraocular pressures, make this an inadvisable method.…”
Section: Methods Used To Reduce Myalgiamentioning
confidence: 99%
“…A wide range of doses of succinylcholine have been studied with conflicting results. Succinylcholine 0.25 mg.kg -1 was shown to be as effective as 0.5 mg.kg -1 3 , although 1.5 mg.kg -1 and 3 mg.kg -1 were both found to be better than 0.5 mg.kg -1 with no significant difference between the two higher doses 24 . Similarly 0.25 and 0.5 mg.kg -1 were not only inferior to 1 mg.kg -1 but also inferior when compared with mivacurium 0.2 mg.kg -1 22 .…”
Section: Discussionmentioning
confidence: 82%